Educação em Foco: entrevista Petronilha B. G. e Silva - Santos, Tarlei de Lima (Universidade Federal de São Carlos, 2023)
Considering the implementation of Affirm Actions - such as the reservation of job vacancies for blacks in higher education -, the relatively recent public policies and, therefore, the natural production opposition of conservatives and reactionaries in society, this aims at a podcasting that seeks to promote the society Young people from the lower classes recognize and use their rights to reserve places in universities. Therefore, the objective of this work is to contribute to the social recognition of the legality of affirmative actions to reserve vacancies. In order to do so, we interviewed a researcher of recognized authority on the subject: Petronilha B. G. e Silva - former counselor of the Higher Education Education Chamber of the National Council of Education and rapporteur of the Opinion CNC/CP 3/2004 that establishes the National Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro Brazilian and African History and Culture. As for the method, we chose the oral genres: scientific interview and life experience report; we opted for the narrative structure understood as deductive. Thus, considering that the burden of argument is on those who intend to establish policies of action, the interview was prepared in order to obtain an exposition of the argument, later an account of the historical process of formation of Brazilian society and, finally, the back to the initial argument.
Education in Focus: Petronilha B. G. e Silva interview
Keywords: Ação afirmativa; Affirmative action; Podcast; Petronilha; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO